eWOM on Tokopedia Marketplace to Enhancing Purchase Decisions: The Role of eWOM Information Usefulness and eTrust - Syahputri, Mawa; Savitri, Citra; Faddila, Syifa Pramudita (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The purpose of this study is to discuss the role of ewom information usefullnes and etrust in mediating ewom information quality, ewom information quantity, ewom information credibility on epurchase decision on Tokopedia.The method used in this study is quantitative, while the analysis technique used is descriptive and verification analysis. The population in this study is all Tokopedia users during 2024, which according to Databoks in 2024 Tokopedia users numbered 18 million.This research was conducted with 130 generation z male respondents, the sampling technique used Hair's theory with SEM-PLS data analysis techniques.This study found that ewom information quality has no effect on etrust and ewom information usefulness, then ewom information quantity has an influence on etrust and ewom information usefulness. eWom information credibility has an influence on etrust and ewom information usefulness. eWom information usefulness and etrust affect ePurchase Decision.This research also provides a view for Tokopedia, which must increase new innovations to attract female consumers, so that its market reach is wider, as it is known that Tokopedia is mostly used by men, it could be due to the lack of information factors needed on Tokopedia